Pendampingan Penulisan Kreatif Bertema Bela Negara melalui Aplikasi Storial.co sebagai Upaya Peningkatan Literasi di Taman Baca Masyarakat (TBM) RW 2 Pradah Kali Kendal Surabaya - Savitri, Adelia; Fitriana, Zuhda Mila; Ravizki, Eka Nanda (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
This creative writing mentoring program aims to improve the skills of writing stories with the theme of defending the country through the Storial.co application so that children can better internalize the values ​​of defending the country based on their daily experiences. In addition, this program also seeks to improve literacy skills from an early age, considering literacy skills are not only at the reading level, but also at the writing level. In addition, writing is also useful for developing creativity in children. This community service program collaborates with the Community Reading Park (TBM) RW 2 Pradah Kali Kendal Surabaya as a partner. The implementation method uses the Storial.co application as a medium for writing creative children's stories with the theme of defending the country. The result of this service program is that the children at TBM RW 2 Pradah Kali Kendal are able to produce creative stories with the theme of defending the country in everyday life, such as love for the environment, love for Indonesian culture, and instilling honesty as the initial capital of an anti-corruption attitude. The output of this program is an e-story product published on the Storial.co page. Publication of works on Storial.co allows their works to be read by the wider community so that they participate in socializing the values ​​of defending the country to children their age from an early age.